Cardinal temperatures for the leaf development of Corymbia citriodora and Eucalyptus urophylla seedlings - Freitas, Cleverson Henrique de; Martins, Fabrina Bolzan; Abreu, Marcel Carvalho (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to estimate cardinal temperatures and phyllochron for the leaf development of the eucalyptus species Corymbia citriodora and Eucalyptus urophylla, in the seedling phase. A field experiment was carried out in a completely randomized design, in a 2x11 factorial arrangement, with the two eucalyptus species, 11 sowing dates, and five replicates, in the municipality of Itajubá, in the state of Minas Gerais, Brazil. The cardinal temperatures – base, optimum, and maximum – for leaf development were, respectively, 8.7, 17.1, and 41.3°C, for C. citriodora, and 11.5, 17.1, and 40.5°C for E. urophylla. The phyllochron of C. citriodora was 62.95°C day per leaf, and that of E. urophylla was 46.03°C day per leaf, which indicates that E. urophylla requires less energy accumulation than C. citriodora for leaf emission in the main stem.